2012
DOI: 10.15835/nsb417259
|View full text |Cite
|
Sign up to set email alerts
|

The C677T Variant in the Methylenetetrahydrofolate Reductase Gene and Idiopathic Spontaneous Abortion in a Romanian Population Group

Abstract: Spontaneous abortions (SA) are a major public health problem and a frequent pregnancy associated disorder. Hereditary thrombophilia and hyperhomocysteinemia are considered to be important factors altering the placental circulation, the in utero development and the evolution of pregnancy. The MTHFR gene (methylenetetrahydrofolate reductase) exhibits an intensely studied polymorphism, C677T, that was repeatedly associated with hyperhomocysteinemia, increased thrombotic risk and was studied in relation with SA su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Several studies showed similar results to ours, regarding the prevalence of heterozygous MTHFR A1298C genotype in VTE: 36.9%, 37.4%, 37%, respectively (40,45,46). A higher frequency of heterozygotes was found in previous Romanian studies regarding thrombophilia in selected groups of patients: 50.1% and 47% in cases with bleeding in the first trimester of pregnancy and repetitive abortions, respectively (41,42). All of the mentioned studies from the literature show the preponderance of the heterozygous form of the MTHFR A1298C polymorphism versus the homozygous form and an absence of association with VTE.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Several studies showed similar results to ours, regarding the prevalence of heterozygous MTHFR A1298C genotype in VTE: 36.9%, 37.4%, 37%, respectively (40,45,46). A higher frequency of heterozygotes was found in previous Romanian studies regarding thrombophilia in selected groups of patients: 50.1% and 47% in cases with bleeding in the first trimester of pregnancy and repetitive abortions, respectively (41,42). All of the mentioned studies from the literature show the preponderance of the heterozygous form of the MTHFR A1298C polymorphism versus the homozygous form and an absence of association with VTE.…”
Section: Discussionsupporting
confidence: 87%
“…26 (24,29,33,35,36) and a 20% increased risk of VTE (37), whereas other studies failed to reveal any significant association (25,(38)(39)(40). Previous Romanian studies regarding thrombophilia in obstetric cases detected frequencies of the homozygous MTHFR 677TT genotype of 19.4% and 19.56% in pregnant patients with haemorrhagic complications and in patients with repetitive spontaneous abortions; no significant associations were found, except for a slightly increased risk for repetitive abortions in the presence of this genotype (41,42). Our result regarding the prevalence of MTHFR 677TT in VTE cases is consistent with these studies.…”
Section: Discussionmentioning
confidence: 94%